Sleep disorders in patients with neoplasm - Pawlicki, Mateusz; Łopuszyńska, Anna; Kozioł, Magdalena; Krasa, Aleksandra; Piekarska, Ewa; Piecewicz-Szczęsna, Halina (Journal of Education, Health and Sport, 2020)
Introduction: Sleep disorders are a big group of disturbances affecting many people in the world. They can appear as insomnia, interrupted sleep, worsened sleep quality or trouble falling asleep. Although they may not seem very dangerous, they lead to various unpleasant complications and even diseases. Cancer is said to be one of the possible sources of the problem. Results: Studies show relationship between cancer and sleep disruptions. They are frequent in lung, head and neck, gynecologic and breast neoplasms. Patients report higher scores of Pittsburgh Sleep Quality Index, insomnia severity scale and Epworth Sleepiness Scale meaning that they can be considered as poor sleepers. In addition, they often develop psychiatric disorders which are linked with higher risk of sleep problems. Conclusions: According to many research, cancer often comes with somnipathies. It should be taken into consideration when planning oncologic treatment and care to obtain the best effects of the therapy.